2019
DOI: 10.1111/cod.13270
|View full text |Cite
|
Sign up to set email alerts
|

Don't forget the sponge

Abstract: 3-diphenylguanidine, carba mix, case report, diphenyl thiourea, occupational allergic contact dermatitis, rubber accelerator, surgical sponge Less well-recognized sources of rubber accelerators, including surgical scrub sponges, are important exposures to consider in surgical personnel experiencing occupationally induced hand and/or forearm dermatitis. ISAAC ET AL. 149 CASE REPORT A 30-year-old man presented with 8 years of bilateral hand dermatitis that started during medical school and continued into his sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Contact dermatitis from thioureas has been described in response to occupational products in health care, including tourniquets used for phlebotomy 3 and surgical scrub sponges. 4 To our knowledge, our case represents the first reported thiourea-associated contact dermatitis from a gun holster and highlights the importance of considering exposure to neoprene in evaluation of patients in law enforcement professions. Some cases of allergic contact dermatitis have been reported to improve in response to treatment with dupilumab, 5 which functions by blocking interleukin 4 receptor α and attenuating T H 2 immune responses.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Contact dermatitis from thioureas has been described in response to occupational products in health care, including tourniquets used for phlebotomy 3 and surgical scrub sponges. 4 To our knowledge, our case represents the first reported thiourea-associated contact dermatitis from a gun holster and highlights the importance of considering exposure to neoprene in evaluation of patients in law enforcement professions. Some cases of allergic contact dermatitis have been reported to improve in response to treatment with dupilumab, 5 which functions by blocking interleukin 4 receptor α and attenuating T H 2 immune responses.…”
Section: Discussionmentioning
confidence: 63%
“…Case reports and series have described contact dermatitis in response to products containing thioureas including neoprene orthopedic supports and sports equipment, such as wet suits and rubber shoes. Contact dermatitis from thioureas has been described in response to occupational products in health care, including tourniquets used for phlebotomy 3 and surgical scrub sponges 4 . To our knowledge, our case represents the first reported thiourea-associated contact dermatitis from a gun holster and highlights the importance of considering exposure to neoprene in evaluation of patients in law enforcement professions.…”
Section: Discussionmentioning
confidence: 73%
“…In the USA, a recent study found that carbamates represented the most common accelerators in medical and surgical gloves, whereas thiurams were used in a much smaller minority [105]. In addition to gloves, HCWs may also be exposed to rubber compounds through contact with medical supplies such as syringes, tubing, and catheters [99], as well as surgical scrub sponges [106].…”
Section: Glovesmentioning
confidence: 99%
“…Eine experimentelle Studie ergab, dass die Anwendung von Händedesinfektionsmitteln mit Alkohol vor dem Anziehen von DPG-haltigen Polyisopren-Handschuhen die auf den Händen nachzuweisende Menge an DPG erhöhte; bei Anwendung von künstlichem Schweiß zum Vergleich wurden 84 % des DPG innerhalb der ersten 10 min des Tragens freigesetzt [183]. Außerdem können chirurgische Schwämme, die zur Reinigung vor dem Anziehen der Handschuhe verwendet werden, ebenfalls Beschleuniger enthalten und zu einer berufsbedingten ACD der Hände beitragen, wie im Fall eines US-amerikanischen Chirurgen, der für DPG sensibilisiert war [184]. In einer belgischen Studie mit 44 Beschäftigten des Gesundheitssektors reagierten 86 % positiv auf DPG, was die Bedeutung dieses Allergens unterstreicht [185].…”
Section: Ergebnisseunclassified